SKRINING FITOKIMIA EKSTRAK DAUN DAN RANTING GLODOKAN TIANG (Polyalthia longifolia L.) - Yunita; Nadiaro Risky Nasution; Rozalia; Musfirah Handayani; Desy Kurniawati; Della Rosalynna Stiadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to identify the secondary metabolite compounds present in leaf and twig extracts of glodokan tiang (Polyalthia longifolia L.) using phytochemical screening and Fourier Transform Infrared (FTIR) analysis. Dried, powdered samples were extracted by maceration with ethyl acetate and 96% ethanol. The extects were qualitatively screened for steroids, terpenoids, alkaloids, phenolics, flaavonoids, and saponins. FTIR analysis (4000-450 cm-1) was used to identify functional groups. Both leaf and twig extracts contained various secondary metabolites, with 96% ethanol extracts showing a broader range of compounds than ethyl acetate extracts. Ethanol leaf extract tested positive for steroids, terpenoids, alkaloids, flavonoids, and saponins. FTIR spectra confirmed the presence of O-H, C-H, C=O, and C-O functional groups, supporting the existence of bioactive secondary metabolites. These findings indicate that glodokan tiang leaves and twigs are promising natural sources of bioactive compounds, and that 96% ethanol is a more effective solvent for extracting secondary metabolites.